Intermediate step of cohesin’s ATPase cycle allows cohesin to entrap DNA - Çamdere, Gamze Ö. (Proc Natl Acad Sci U S A, 2018)
Cohesin is a four-subunit ATPase in the family of structural maintenance of chromosomes (SMC). Cohesin promotes sister chromatid cohesion, chromosome condensation, DNA repair, and transcription regulation. Cohesin performs these functions as a DNA tether and potentially a DNA-based motor. At least one of its DNA binding activities involves entrapment of DNA within a lumen formed by its subunits. This activity can be reconstituted in vitro by incubating cohesin with DNA, ATP, and cohesin loader. Previously we showed that a mutant form of cohesin (DE-cohesin) possesses the ability to bind and tether DNA in vivo. Using in vitro reconstitution assays, we show that DE-cohesin can form stable complexes with DNA without ATP hydrolysis. We show that wild-type cohesin with ADP aluminum fluoride (cohesin(ADP/AlFx)) can also form stable cohesin–DNA complexes. These results suggest that an intermediate nucleotide state of cohesin, likely cohesin(ADP-Pi), is capable of initially dissociating one interface between cohesin subunits to allow DNA entry into a cohesin lumen and subsequently interacting with the bound DNA to stabilize DNA entrapment. We also show that cohesin(ADP/AlFx) binding to DNA is enhanced by cohesin loader, suggesting a function for loader other than stimulating the ATPase. Finally, we show that loader remains stably bound to cohesin(ADP/AlFx) after DNA entrapment, potentially revealing a function for loader in tethering the second DNA substrate. These results provide important clues on how SMC complexes like cohesin can function as both DNA tethers and motors.